2001
DOI: 10.4152/pea.200103145
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrodes in Artificial Synapses: a Study of Oxidative Stress at the Cellular Level

Abstract: Platinized carbon micro electrodes {-10 (tm diameter), positioned close {~ 5 urn) to the cell membrane of a human fibroblast, the ensemble constituting a semi-artificial synapse, are used to monitor events at the cellular level. A few tens of femlomoles of reactive oxygen species produced and emitted by the cell upon mechanical pricking with a glass micropipette (~ Î um diameter) are released into the liquid film of some hundred femtoliires comprised between the cytoplasmic membrane and the electrode surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Voltammetry of 2,6-diphenylpyrylium perchlorate on platinum at scan rates in excess of 10 5 V s À1 has been published by Amatore [23,25], in which the reverse peak has been resolved. It was noted that, due to ohmic distortions, a precise determination of k EC 2 directly from the fast-scan data was not possible, so an indirect method was used.…”
Section: Digisim Modelling Of the Ec 2 Mechanismmentioning
confidence: 98%
See 2 more Smart Citations
“…Voltammetry of 2,6-diphenylpyrylium perchlorate on platinum at scan rates in excess of 10 5 V s À1 has been published by Amatore [23,25], in which the reverse peak has been resolved. It was noted that, due to ohmic distortions, a precise determination of k EC 2 directly from the fast-scan data was not possible, so an indirect method was used.…”
Section: Digisim Modelling Of the Ec 2 Mechanismmentioning
confidence: 98%
“…A diffusion coefficient of D = 1.2 ± 0.1 · 10 À5 cm 2 s À1 was established by applying the fitting methods previously described [29,30]. We are unaware of any previously published value for this constant [23][24][25]. Fig.…”
Section: Microdisc Potential Step Chronoamperometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of single microelectrodes has revolutionised both the spatial and temporal aspects of electrochemistry, for example, allowing microscopic imaging of electrode surfaces [1][2][3] and access to hitherto inaccessible short timescales [4][5][6]. Nevertheless for many practical purposes, notably analytical measurements [7][8][9][10] and studies of metal nucleation and growth phenomena [11,12], it has proved convenient and advantageous to employ arrays containing hundreds or even thousands [13] of microdisc electrodes wired in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on this mechanism have reported surprisingly different values of k dim , from 2.5 10 7 m À1 s À1[6] to 2.5 10 9 m À1 s À1 [7,8] .…”
mentioning
confidence: 99%